Method for converting lignocellulosic materials into organic liquefaction products
By using a non-supported molybdenum sulfide catalyst containing specific metal elements during the thermochemical liquefaction process and liquefaction under high pressure hydrogen conditions, the problems of high oxygen content and instability in biomass liquefaction are solved, and a liquefied product with low oxygen content and thermal stability is achieved.
Patent Information
- Application Number
- JP2024555284
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-17
- Filing Date
- 2023-03-17
- Publication Date
- 2025-04-11
Smart Images

Figure 2025509801000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel process for the conversion of solid lignocellulosic starting materials to organic liquefaction products, to a novel molybdenum sulfide catalyst for use in said process, and to a method for making said catalyst. [Background technology]
[0002] It is well known that thermochemical processes such as pyrolysis and hydrothermal liquefaction (HTL) can depolymerize total lignocellulosic biomass as well as lignocellulosic biomass fractionation products, such as kraft lignin, and other renewable by-streams from the agriculture, forestry, and pulp and paper industries, often producing liquefaction products collectively referred to as "bio-oils" or "bio-crude". These products can then be upgraded using hydrotreating and hydrocracking techniques more or less similar to those used to upgrade fossil crude oil and its distillates in oil refineries, to obtain mixtures of hydrocarbons that can be used, for example, as transportation fuel components.
[0003] Problems frequently encountered in the thermochemical liquefaction (pyrolysis or HTL) of biomass include, for example, the relatively high oxygen content and the resulting spontaneous reactivity of the depolymerized product mixture, i.e., product mixtures containing reactive phenolic derivatives combined with aldehydes and ketones, among other molecular structure classes, which together lead to more or less severe repolymerization during storage and / or heating. Other problems are, for example, the formation of char and the loss of highly volatile organic components, which ultimately results in a lower than desired carbon yield of the upgraded hydrocarbon fuel components.
[0004] An example of a further problem is the high content of water in the resulting product. In addition, this water is often very difficult or impossible to remove by phase separation due to the polarity of many of the organic components in bio-oil. Distillation to remove the water is precluded by lack of stability during heating due to the repolymerization problems mentioned above. Furthermore, the high water content, combined with the acidity of bio-oil, creates a situation where bio-oil is highly corrosive to standard materials of construction used in refinery upgrade equipment. As illustrated in the figure, pyrolysis of lignocellulosic materials results in an oxygen content in the condensable fraction of 20->40%. The same condensable fraction typically has a pH value of about 2-3 as a result of the high content of carboxylic acids and water. Overall, this means that the total oxygen and water content is not significantly lower than in the more stable, non-depolymerized, dried but otherwise untreated, and significantly less acidic lignocellulosic biomass.
[0005] To sum up, although pyrolysis or HTL often results in a pumpable liquid bio-oil, the resulting bio-oil or bio-crude products are both corrosive and unstable with respect to storage and heating due to spontaneous repolymerization problems. In addition, these products currently exhibit poor or no compatibility with the fossil or other renewable feedstocks for easy and flexible co-processing within standard refinery infrastructure. These characteristics clearly pose problems when developing practical and robust full-scale processes for upgrading pyrolysis and / or HTL bio-oils, both individually and through co-processing, into hydrocarbon transportation fuels and chemicals.
[0006] With regard to hydrocracking catalysts that can be used to fully and / or partially upgrade renewable feedstocks and feedstock mixtures, there are many different base and precious metal catalysts described in the literature that have been used to upgrade lignocellulosic derived bio-oil or other materials to hydrocarbon-rich product mixtures with greater or lesser success. These catalysts can be based on a single metal or can consist of a combination of different metals or metal compounds, supported or unsupported on chemically inert or reactive support materials.
[0007] In summary, there is a need for an improved, simple and robust process that is applicable to lignocellulosic feedstocks and suitable for upscaling. These and other objectives will become apparent from the summary and from the description of specific embodiments below. As will be apparent to one of skill in the art, one or more embodiments may meet certain objectives, while one or more other embodiments may meet certain other objectives. Summary of the Invention [Means for solving the problem]
[0008] The present disclosure makes available a new hydroliquefaction process, and a new catalyst for use in said process, as well as a method for producing said catalyst. According to a first aspect, the process for converting lignocellulosic starting material to organic liquefaction products is characterized by mixing lignocellulosic starting material, optionally from a single source or a mixture of related starting materials, with an amorphous and unsupported molybdenum sulfide catalyst containing one or more of the following elements: iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), and a cofeed, and exposing it to stoichiometric or greater amounts of hydrogen, high pressure, and a temperature of 270°C to 450°C, thereby producing an organic liquefaction product. Effect of the Invention
[0009] The process according to the present disclosure is a hydroliquefaction process, which converts lignocellulosic biomass from a solid phase into organic liquefaction products that may, for example, subsequently be converted into fuels or used to produce chemicals. An advantage of the process according to the present disclosure is that it may be carried out at surprisingly low temperatures, which in turn is advantageous in terms of reduced energy consumption, which in turn provides potential cost benefits.
[0010] A further advantage is that the oxygen content of the organic liquefaction product, which may be an intermediate intended for further conversion to one or more end products, is low, making the organic liquefaction product a more thermally stable intermediate and stable for storage.
[0011] In the prior art of lignocellulosic hydroliquefaction, the typical carrier oil was a hydrogen donor solvent, such as tetralin.
[0012] In comparison to the conventional use of CoMo catalysts for liquefying biomass (see "Burton et al 1986, "Catalytic Hydroliquefaction of Lignocellulosic Biomass", International Journal of Solar Energy), the process of the present invention does not require the use of a hydrogen donor solvent, e.g. tetralin, as a co-feed, which can be e.g. paraffinic. A further advantage of the current process compared to the prior art is that the process operates at a high solid lignocellulose content. A further advantage is that the organic liquefaction product has a better quality, e.g. compared to the product according to Burton et al., who obtained a significant amount of asphaltenes from the process.
[0013] The co-feed may thus include co-feeds other than tetralin.
[0014] The cofeed is optionally substantially free of tetralin, i.e., at least 99% of the cofeed is free of tetralin, or at least 99.5% is free of tetralin. When the cofeed is substantially free of tetralin, this means that tetralin is not converted as a cofeed during the process, but small amounts of tetralin residues may be formed during the process. Optionally, the cofeed does not contain tetralin. The fact that the process can be carried out with a cofeed that is substantially free of or free of tetralin allows for the use of cheaper, conventional, and easily accessible refinery feedstocks, or the use of recycled products or product fractions, thus providing flexibility in the choice of cofeed, since the cofeed is not required to have a strong hydrogen donor capacity in order to obtain a high degree of conversion of the solid lignocellulosic starting material.
[0015] The liquid phase additionally exhibits improved physical properties, providing process benefits during subsequent process steps, such as pumping, and the resulting intermediate liquid product can also be more easily incorporated as a feedstock into conventional refineries due to its lower oxygen content.
[0016] A further advantage is that the low oxygen content in the organic liquefaction products obtained by the process according to the present disclosure may reduce the exotherm during complete hydrodeoxygenation to form the hydrocarbon end products.
[0017] "Elevated pressure" means pressure above atmospheric pressure.
[0018] The molar fraction of sulfur (S) relative to the content of molybdenum (Mo) in the amorphous and unsupported molybdenum sulfide catalyst may be from 0.1 to 2.3. It has surprisingly been found by the inventors that the catalysts disclosed herein enable liquefaction of lignocellulosic starting materials in high yields.
[0019] In the amorphous and unsupported molybdenum sulfide catalyst, the molar fraction of sulfur (S) relative to the molar fraction of molybdenum (Mo) may be 0.1 to 1.0. In an embodiment, the molar fraction of sulfur (S) may be 0.3 to 0.99, for example, 0.5 to 0.95.
[0020] In the amorphous and unsupported molybdenum sulfide catalyst, the molar fraction of the one or more elements, i.e., iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru) relative to the molar fraction of molybdenum (Mo) is 0.1 to 0.3, and optionally 0.1 to 0.2.
[0021] An important advantage of the catalyst being an unsupported, unsupported catalyst is that it can be added at a different process stage, for example after the starting materials have been ground, and thus intimately mixed with them.
[0022] Preferably, the catalyst is introduced into the mixture of lignocellulosic starting material in a liquid cofeed, optionally in the form of a slurry of catalyst particles in a pure liquid or a mixture of different liquid components. The liquid cofeed may be a hydrocarbon cofeed.
[0023] The co-feed may be selected from vegetable oils and vegetable fats, such as tall oil and tall oil pitch, pyrolysis oils, HTL oils, animal fats, fatty acids, fossil or renewable liquid hydrocarbons, and / or recycles or recycled products of the products obtained in said processes or fractions of the products obtained in said processes.
[0024] In an exemplary embodiment, the cofeed is a mixture of vegetable oil and / or animal fat with fossil or renewable hydrocarbons.
[0025] The total feed may consist of 5-90% by weight solid biomass, preferably 10-80% by weight solid biomass. The total feed may consist of 60-80% by weight solid biomass, or 10-35% by weight solid biomass. This implies a liquid content of 10% by weight, preferably up to 65% by weight. This may provide process advantages such as a pumpable slurry.
[0026] The lignocellulosic starting material may have a dry content of greater than 50% by weight, preferably between 70 and 95% by weight, most preferably between 80 and 92% by weight.
[0027] The lignocellulosic starting material may be selected from forest residues selected from wood chips and / or sawdust, bark and / or roots, wood that has been subjected to a drying or torrefaction process, lignocellulosic originating from agriculture, such as straw from crops such as oats, wheat, barley and rye, corn stover, grasses and herbs, fodder crops, oat husks, rice husks, construction waste containing at least 50% by weight of material of lignocellulosic origin, and mixtures thereof.
[0028] According to another embodiment, which can be freely combined with the above aspects and embodiments, the lignocellulosic starting material has not been subjected to a thermochemical treatment, such as pyrolysis or hydrothermal liquefaction, prior to being subjected to said process, thus achieving a more simplified process.
[0029] The organic liquefaction product may have a lower oxygen content than the feed, including the co-feed, and optionally the organic liquefaction product may have an oxygen content at least 5% by weight lower, such as at least 10% by weight lower, than the feed, including the co-feed, where the feed includes all of the starting materials.
[0030] According to another embodiment, which can be freely combined with the above aspects and embodiments, the operating pressure is between 50 and 300 bar, which allows improving and accelerating the liquefaction process carried out in the temperature range of the present process.
[0031] The operating pressure is optionally between 60 and 300 bar.
[0032] The mixture may be subjected to a temperature of 300° C. to 380° C. Operating temperatures within the preferred range provide improved liquid yields.
[0033] The process may or may not be split into two or more hydrotreating reactors with a flat or ascending temperature profile. The process may thus include a first hydrotreating step followed by at least a second conversion step.
[0034] In the second hydroprocessing reactor the operating temperature may be between 270 and 450°C, optionally the operating temperature in the second hydroprocessing reactor may be above 350°C, for example between 350°C and 450°C.
[0035] In a preferred embodiment, hydrotreating is carried out in two or more reactors in series, where each subsequent reactor is operated at a higher temperature than the first reactor. Preferably the process is carried out in three reactors in series, and the temperature of the first reactor is selected from 270-350°C, the temperature of the second reactor is selected from 340-400°C, and the temperature of the third reactor is selected from 380-400°C.
[0036] A second aspect of the present disclosure is a molybdenum sulfide catalyst comprising one or more of the following elements (E): iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), the catalyst having an empirical formula for molybdenum (Mo), the one or more elements (E), and sulfur (S): Mo x E y S z having Regarding a molybdenum sulfide catalyst, in the above, x = 1, 0.1 < y < 0.3, and z ≤ 2.3.
[0037] An important advantage of the catalyst of the present invention is that its production is relatively inexpensive and easy. Furthermore, since it can be used as such without being bonded to a carrier, the catalyst can be added at different process stages.
[0038] For example, in an amorphous and unsupported molybdenum sulfide catalyst, the molar fraction of sulfur (S) relative to the molar fraction of molybdenum (Mo) is from 0.1 to 2.3. The molar fraction of sulfur (S) relative to the molar fraction of molybdenum (Mo) in the amorphous and unsupported molybdenum sulfide catalyst may be ≤ 1.0, optionally from 0.1 to 1.0. In an embodiment, the sulfur content is from 0.3 to 0.99, for example from 0.5 to 0.95.
[0039] In the amorphous and unsupported molybdenum sulfide catalyst, the molar fraction of the one or more elements, namely iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), relative to the molar fraction of molybdenum (Mo) may be from 0.1 to 0.3, optionally from 0.1 to 0.2.
[0040] Preferably, the catalyst is substantially amorphous as determined by X-ray powder diffraction analysis and optical microscopy using polarization. Optionally, the catalyst is amorphous as determined by X-ray powder diffraction analysis.
[0041] According to an embodiment of the second aspect, the particle size distribution of the catalyst has a median of 1-500 μm as determined by laser diffraction. Preferably, the particle size distribution of the catalyst has a median of 1-200 μm as determined by laser diffraction. The advantage of such a particle size distribution is improved dispersion in the feed slurry and availability of the catalyst in the entire reactor volume compared to supported or larger catalyst particles that are only available in the reaction zone. Moreover, such a particle size distribution makes the catalyst accessible to larger molecules and enhances activity.
[0042] A third aspect of the present disclosure relates to a process for converting a lignocellulosic starting material into an organic liquefaction product, comprising exposing a mixture of the lignocellulosic starting material, a catalyst according to the second aspect and embodiments thereof, and a cofeed to stoichiometric or greater hydrogen, elevated pressure, and a temperature in the range of 270°C to 450°C to produce the organic liquefaction product.
[0043] A fourth aspect is a process for producing a molybdenum sulfide catalyst containing one or more of the following elements (E): iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), comprising: - forming a first reaction mixture by combining MoO3, (NH4)2S, and water; - pressurizing the first mixture using hydrogen gas and heating and stirring the mixture; - forming a second mixture by adding a hydrocarbon fraction having a kinematic viscosity of less than 2.0 CSt@40°C and metal salts of Fe and / or W and / or Co and / or V and / or Ru, such as sulfates and / or nitrates of Fe, W, Co, V and Ru, to the first mixture at an appropriate pressure and temperature; - pressurizing said second mixture with hydrogen gas and heating said second mixture using a suitable temperature gradient; - removing water and a portion of the hydrocarbon fraction by reducing the pressure of the second mixture and heating the residual hydrocarbons to a suitable temperature; and - recovering said catalyst in the form of a slurry with residual hydrocarbons; The present invention relates to a process for producing a molybdenum sulfide catalyst, comprising the steps of:
[0044] In the step of forming a second mixture, one or more of the following elements (E), iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), are added to a mixture having an empirical formula for molybdenum (Mo), the one or more elements (E), and sulfur (S): Mo x E y S z may be added in an amount to provide a catalyst having In the above, x=1, 0.1 <y<0.2、そしてz≦2.3である。
[0045] For example, the molar fraction of sulfur (S) relative to the molar fraction of molybdenum (Mo) in the unsupported molybdenum sulfide catalyst is 0.1 to 2.3. The molar fraction of sulfur (S) relative to the molar fraction of molybdenum (Mo) in the amorphous and unsupported molybdenum sulfide catalyst may be 0.1 to 1.0. In an embodiment, the sulfur content is 0.3 to 0.99, for example, 0.5 to 0.95.
[0046] In the amorphous and unsupported molybdenum sulfide catalyst, the molar fraction of the one or more elements, i.e., iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru) relative to the molar fraction of molybdenum (Mo) may be 0.1 to 0.3, and optionally 0.1 to 0.2.
[0047] A kinematic viscosity of the hydrocarbon fraction less than 2.0 CSt @ 40°C facilitates removal of water by boiling and separation by distillation to obtain a catalyst that is free of water, or at least substantially free of water.
[0048] Further aspects and embodiments will become apparent to those of ordinary skill in the art upon examination of the drawings and the following detailed description and examples.
[0049] Aspects and embodiments are described below, by way of example, with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0050] [Figure 1] FIG. 1 shows the XRPD-diffractogram of the catalyst according to Example 1. [Diagram 2] FIG. 2 shows the particle size distribution of the catalyst according to Example 1. [Diagram 3] FIG. 3 shows TGA data for the organic liquid product phase of Example 2. [Figure 4] FIG. 4 shows TGA data for the THF soluble liquefied phase of Example 2. [Diagram 5] FIG. 5 shows TGA data for the organic liquid product phase of Example 4. [Figure 6] FIG. 6 shows TGA data for the THF soluble liquefied phase of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] In considering the detailed description, it should be understood that the terminology employed herein is used only for the purpose of describing particular embodiments and is not intended to be limiting, as the scope of these aspects and embodiments shall be limited only by the appended claims and their equivalents.
[0052] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include the plural forms unless the context clearly indicates otherwise.
[0053] The terms "lignocellulosic material," "lignocellulosic starting material," and "lignocellulosic feed" are used herein to include all whole, unfractionated lignocellulosic materials that consist substantially of cellulose, hemicellulose, and lignin. Depending on the geographic location, different materials are available, such as agricultural residues (e.g., corn stover, crop straw, and bagasse), herbaceous crops (e.g., alfalfa, switchgrass), softwood and hardwood, short rotation woody crops, preheated and / or torrefied wood, forest residues (bark and branches, roots, and tops), and other waste products (municipal and industrial waste products that contain whole lignocellulosic biomass, such as waste wood used in the construction industry and / or packaging of goods). The inventors have tested ground up municipal waste, including pine sawdust with various dry matter contents, ground roots and branches of spruce, fresh spruce needles, fresh pine bark, and wood, plastic, sand, metal, and paint residues.
[0054] The terms "unsupported" and "carrier-free" mean that the catalytic material, such as the sulfided Mo catalyst, is not deposited on any solid carrier or support material.
[0055] The fact that a catalyst is "amorphous" is intended to mean that the catalyst is substantially amorphous or amorphous as determined by X-ray powder diffraction analysis.
[0056] The distinction between amorphous and crystalline materials, as determined by X-ray powder diffraction analysis, is that crystalline materials produce sharp peaks in the XRD pattern, whereas amorphous materials do not produce any sharp peaks.Thus, amorphous catalysts, as determined by X-ray powder diffraction analysis, do not produce any sharp peaks in the XRD pattern.
[0057] Although "hydrocarbon fraction" and "hydrocarbon phase" herein relate to the liquid hydrocarbon fraction that may be recovered at room temperature following the processes disclosed herein, this definition does not exclude that additional more volatile hydrocarbons may be condensed at lower temperatures and included in this fraction.
[0058] The resulting organic liquefaction product may be liquid from room temperature up to 500° C. The organic liquefaction product may comprise one or more organic liquid phases.
[0059] "Solid residue" herein means the residual solids separated from the organic liquefaction product after hydroliquefaction of lignocellulosics, as illustrated in the test examples below. According to a first aspect, this process for converting lignocellulosic starting material to organic liquefaction product is characterized in that lignocellulosic starting material, consisting of a single source or a mixture of related starting materials, is mixed with an amorphous and unsupported molybdenum sulfide catalyst containing one or more of the following elements (E): iron (Fe), tungsten (W), cobalt (Co), vanadium (V) and ruthenium (Ru), and optionally a cofeed, and exposed to stoichiometric or greater amounts of hydrogen, elevated pressure, and temperatures between 270°C and 450°C to produce the organic liquefaction product.
[0060] Preferably, the catalyst according to the present disclosure is an amorphous and unsupported sulfided cobalt-molybdenum catalyst.
[0061] Preferably, the catalyst is introduced into the mixture of lignocellulosic starting material in the form of a slurry of catalyst particles in a hydrocarbon co-feed.
[0062] A co-feed is present in the process and may be selected from vegetable oils and vegetable fats, such as tall oil and tall oil pitch, pyrolysis oils, HTL oils, animal fats, fatty acids, fossil or renewable liquid hydrocarbons, and / or recycles or recycled products of products obtained in said process or fractions of products obtained in said process.
[0063] The lignocellulosic starting material may have a dry content of greater than 50% by weight, preferably between 70 and 95% by weight, most preferably between 80 and 92% by weight.
[0064] The lignocellulosic starting material may be selected from forest residues selected from wood chips and / or sawdust, bark and / or roots, wood that has been subjected to a drying or torrefaction process, lignocellulosic originating from agriculture, such as straw from crops such as oats, wheat, barley and rye, corn stover, grasses and herbs, fodder crops, oat husks, rice husks, construction waste containing at least 50% by weight of material of lignocellulosic origin, and mixtures thereof.
[0065] With regard to materials that have been subjected to a drying or torrefaction process, it is emphasized that torrefaction is considered here simply to be a drying process, i.e. moisture removal, and not a thermochemical process in the strict sense.
[0066] According to another embodiment, which can be freely combined with the above aspects and embodiments, the lignocellulosic starting material has not been subjected to a thermochemical treatment, such as pyrolysis or hydrothermal liquefaction, prior to being subjected to said process.
[0067] According to yet another embodiment that can be freely combined with the above-described aspects and embodiments, the operating pressure is optionally 50 to 300 bar, for example 60 to 300 bar. When operating the process in batch mode, the initial pressure is set based on the available headspace and to ensure a stoichiometric excess of hydrogen, for example, set and increased at an initial pressure of 120 bar at ambient temperature, and allowed to stabilize at 150 to 300 bar, preferably 250 bar. When operating the process continuously, the pressure is preferably set to 70 to 180 bar, more preferably 90 to 160 bar.
[0068] The mixture may be exposed to a temperature of 300 °C to 380 °C. The operating temperature within the preferred range provides an improved liquid yield.
[0069] A second aspect of the present disclosure relates to a molybdenum sulfide catalyst comprising one or more of the following elements (E), namely iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), wherein the catalyst has an empirical formula with respect to molybdenum (Mo), said one or more elements (E), and sulfur (S), namely Mo x E y S z having wherein, in the above, x = 1, 0.1 < y < 0.3, and z ≤ 2.3, relating to the molybdenum sulfide catalyst.
[0070] Preferably, the catalyst is substantially amorphous as determined by X-ray powder diffraction analysis. Optionally, the catalyst is amorphous as determined by X-ray powder diffraction analysis.
[0071] Preferably, the catalyst according to the present disclosure is an amorphous and unsupported cobalt-molybdenum sulfide catalyst.
[0072] According to one embodiment of the second aspect, the particle size distribution of the catalyst has a median of 1 to 500 μm as determined by laser diffraction. Optionally, the particle size distribution of the catalyst has a median of 1 to 200 μm as determined by laser diffraction.
[0073] A third aspect of the present disclosure relates to a process for converting a lignocellulosic starting material into an aqueous phase and a hydrocarbon phase, comprising exposing a mixture of the lignocellulosic starting material, a catalyst according to the second aspect and embodiments thereof, and a cofeed to stoichiometric or greater hydrogen, elevated pressure, and a temperature between 270°C and 450°C to produce one or more liquid phases and / or aqueous and hydrocarbon phases.
[0074] A fourth aspect is a process for producing a catalyst according to the second aspect and embodiments thereof, comprising the steps of: - forming a first reaction mixture by combining MoO3, (NH4)2S, and water; - pressurizing the first mixture using hydrogen gas and heating and stirring the mixture; - forming a second mixture by adding a hydrocarbon fraction having a kinematic viscosity of less than 2.0 CSt@40°C and metal salts of Fe and / or W and / or Co and / or V and / or Ru, such as sulfates and / or nitrates of Fe, W, Co, V and Ru, to the first mixture at an appropriate pressure and temperature; - pressurizing said second mixture with hydrogen gas and heating said second mixture using a suitable temperature gradient; - removing water and a portion of the hydrocarbon fraction by reducing the pressure of the second mixture and heating the residual hydrocarbons to a suitable temperature; and - recovering said catalyst in the form of a slurry with residual hydrocarbons; The present invention relates to a process for producing a catalyst, comprising the steps of:
[0075] The lignocellulosic starting material is optionally subjected to mechanical pretreatment to simplify the handling of the material and to increase the surface to volume ratio. Suitable pretreatment operations include milling, chipping and grinding. In tests carried out by the inventors so far, starting material of various particle sizes, for example below 10 mm, for example between 0.5 mm and 10 mm, has been tested, preferably the particle size of the lignocellulosic starting material is below 2 mm. The results suggest that the process is capable of handling all these particle sizes and that the particle size does not appear to be a determining factor.
[0076] In the step of forming the second mixture, the metal salts of Fe and / or W and / or Co and / or V and / or Ru, for example sulfates and / or nitrates of Fe, W, Co, V and Ru, are reacted with molybdenum (Mo), the one or more elements (E), and sulfur (S) according to an empirical formula: Mo x E y S z may be added in an amount to provide a catalyst having In the above, x=1, 0.1 <y<0.3、そしてz≦2.3である。
[0077] During the development of this disclosure, the inventors constructed a laboratory scale batch process, as detailed in the Examples, that allowed for testing lignocellulosic starting materials, comparing new catalysts with other known catalysts, and testing different process parameters. The process may be validated in semi-batch mode.
[0078] Working Example Analysis method For example, the method described by L. Akim et al. Holzforschung 2001, 55, 386-390 was used on a Bruker Avance 500 UltraShield NMR spectrometer. 31Hydroxyl number determination was performed by P-NMR to analyze the amount of hydroxyl groups belonging to aliphatic alcohols (aliphatic OH), phenols (aromatic OH), and carboxylic acid OH groups. 1 H-NMR was used to characterize the relative amounts of protons that are part of aromatic, aliphatic, ether / alcohol, aldehyde, ketone, carboxylic acid, and olefinic functional groups in the resulting product mixture.
[0079] The boiling point ranges were determined using thermogravimetric analysis on a Mettler-Toledo TGA / SDTA851e instrument.
[0080] This was carried out using a Malvern Mastersizer 2000 laser diffraction instrument.
[0081] X-ray powder diffraction analysis (XRPD) was performed on a PANalytical X'Pert PRO spectrometer. EXAMPLES
[0082] Example 1 Preparation of CoMo catalyst Molybdenum trioxide (40 g), ammonium sulfide (60 mL, 20% w / w in water), and water (122 g) were added to a 1.8 L steel reactor. An inert nitrogen atmosphere was established using three vacuum-nitrogen cycles (nitrogen pressure 6 bar). The reactor was pressurized to 22 bar with hydrogen and the mixture was stirred using a pitch blade stirrer at a tip speed of 2.4 m / s. The jacket temperature was increased to 68° C. and after soaking for 4 hours the temperature was reduced to 38° C. The reactor was depressurized and then an inert atmosphere was established by using vacuum-nitrogen cycles (nitrogen pressure 6 bar). A mixture of n-dodecane (400 mL) and cobalt sulfate heptahydrate (45.9 g, 28.4 w / w% aqueous solution) was added to the reactor. The reactor was sealed and an inert nitrogen atmosphere was established using three vacuum-nitrogen cycles (nitrogen pressure 6 bar) before hydrogen was added to a pressure of 25 bar. The jacket temperature was increased to 210° C. over a period of 6 hours. After 1 hour at temperature, the reactor contents were allowed to cool to room temperature. The reactor was depressurized and then an inert atmosphere was established using vacuum-nitrogen cycles (nitrogen pressure 6 bar). A condenser was attached to the reactor and then water and half the amount of n-dodecane were distilled at atmospheric pressure using a low flow rate of ballast nitrogen gas. After distillation, the cooled reactor slurry contents were removed from the reactor and, with the catalyst protected from air, larger particles were removed by sieving through a 280 μm stainless steel sieve. The catalyst was used and stored as a slurry in dodecane with an assay of 26.1% w / w based on triplicate determinations.
[0083] The XRPD-diffractogram of the catalyst based on Example 1 shown in FIG. 1 does not show any XRPD peaks indicative of crystallinity, and the conclusion is that the catalyst based on Example 1 is amorphous.
[0084] Figure 1 shows the XRPD-diffractogram of the CoMoS catalyst according to Example 1, which shows that the catalyst is amorphous.
[0085] Figure 2 shows the particle size distribution of the CoMoS catalyst according to Example 1. To determine the particle size distribution, an aliquot of the catalyst prepared according to Example 1 was dispersed in pure dodecane and analyzed by laser diffraction on a Malvern Mastersizer 2000 after in situ sonication. The results suggest a median particle size of 1.6 μm. EXAMPLES
[0086] Example 2 Hydrodeoxygenation of sawdust using a CoMo catalyst based on Example 1 Milled and sieved pine sawdust (30.01 g, dry matter content 91.5% w / w) and catalyst slurry prepared according to Example 1 (8.40 g, assay of 26.1% w / w in dodecane) were added to a 300 mL stainless steel high pressure reactor. An inert nitrogen atmosphere was established using three vacuum-nitrogen cycles before pressurizing the reactor with hydrogen (120 bar). The reactor contents were heated to 380° C. for 2 hours with stirring. After cooling, depressurization, and establishment of an inert atmosphere by vacuum-nitrogen cycles, the reactor contents were poured into a centrifuge vial and centrifuged at 2.9×10−3 G for 20 minutes. The organic liquid phase, the aqueous phase, and the solid residue phase were separated. Two portions of n-pentane (2×45 mL) and three 45 mL portions of tetrahydrofuran (THF) were used to successively wash the solid residue, the reactor, the lid, and the stirrer. After each wash, the mixture was centrifuged and separated. The n-pentane wash phase was poured into one separate container and the THF-wash phase was poured into another separate container, after which the solvents (n-pentane and THF) were evaporated. After complete work-up, including drying for the pentane and THF phases, the following products were isolated: an organic liquid phase pooled with the contents of the n-pentane wash phase (16.46 g of a light amber liquid, 45% yield w / w calculated on the total feed including dodecane), 8.45 g of an aqueous phase, 1.96 g of a THF-soluble liquefied phase, and 2.59 g of a solid residue. For the organic liquid phase: 1 H data and 31The P-NMR data can be found below (Tables 1 and 2) and the TGA data is shown in Figure 3. 1 H data and 31 The P-NMR data can be found below (Tables 3 and 4) and the TGA data is shown in Figure 4. The NMR results suggest that the THF soluble liquefied phase has a higher oxygen content, and this is confirmed by the elemental analysis data below. The amount of isolated solid material, calculated on the dry biomass, was only 1.4% w / w. Taking into account the sawdust ash content of 0.6%, the amount of solid product is small.
[0087] Elemental analysis data for the organic liquid phase were C 84.1%, H 11.8%, N 0.34%, S 0.0%, O 3.1%, others 0.48%.
[0088] Elemental analysis data for the THF-soluble liquid phase was C 81.9%, H 8.6%, N 0.56%, S 0.14%, O 8.32%, others 0.48%.
[0089] Table 1 shows the organic liquid phase of Example 2. 1 H-NMR (CDCl3) results (normalized integral value) are shown. [Table 1]
[0090] Table 2 shows the organic liquid phase of Example 2. 31 The hydroxyl numbers measured by P-NMR are shown. [Table 2]
[0091] Figure 3 shows the TGA data for the organic liquid product phase of Example 2. The dashed line indicates the boiling range of diesel.
[0092] Table 3 shows the THF soluble liquefied phase of Example 2. 1The results of H-NMR (DMSO-d6) (normalized integral value) are shown. [Table 3]
[0093] Table 4 shows the THF soluble liquefied phase of Example 2. 31 The hydroxyl numbers measured by P-NMR are shown. [Table 4]
[0094] Figure 4 shows the TGA data for the THF soluble liquefied phase of Example 2. The dashed line indicates the boiling range of diesel. EXAMPLES
[0095] Example 3 Preparation of CoMo catalyst - second example The catalyst slurry of Example 1 (23.24 g, 47 mmol) was added to a 300 mL Buchi batch autoclave, followed by DMDS (6.7 mL, 76 mmol). The reactor was sealed and inerted three times using N2 (5 bar), then pressurized to 80 bar using H2. The reaction mixture was stirred at 800 rpm and heated to 300°C during a heating ramp duration of 1 hour, and then left at this temperature for 12 hours. After cooling, the H2S in the headspace gas mixture was trapped by bubbling the headspace into a beaker containing aqueous NaOH (30% w / w). The NaOH solution was then quenched with H2O2 to oxidize the sulfides to sulfates. The black slurry mixture inside the reactor was transferred to a vial. The reactor and stirrer were rinsed with 20 mL of dodecane. The slurry dry catalyst assay was determined based on three individual samples amounting to 14.11% w / w. EXAMPLES
[0096] Example 4 Hydrodeoxygenation of sawdust using a CoMo catalyst based on Example 3 Sawdust with a particle size distribution of <0.28 mm (30.0 g, dry matter content 91.5% w / w) and catalyst slurry prepared according to Example 3 (10.12 g, assay adjusted to 14.11% w / w - 28.03% w / w in dodecane before use by centrifuging and removing a portion of the dodecane using a pipette, dry catalyst weight 2.84 g) were mixed at room temperature in a high-pressure reactor. An inert nitrogen atmosphere was established using vacuum-nitrogen cycles before pressurizing the reactor with hydrogen (116 bar). The reaction mixture was heated to 320°C and maintained at that temperature for 240 minutes. The maximum operating pressure during the reaction was 245 bar. After using the work-up procedure described in Example 2, 11.39 g of a dark brown organic liquid phase (28% yield w / w calculated on the total feed), 5.99 g of an aqueous phase, 6.68 g of a THF-soluble liquefied phase (17% yield w / w calculated on the total feed), and 3.17 g of a solid residue were isolated. 1 H data and 31 P-NMR data can be found in Tables 5 and 6 below, and TGA data is shown in Figure 5. 1 H data and 31 The P-NMR data can be found below (Tables 7 and 8) and the TGA data is shown in Figure 6. The NMR results suggest that the THF soluble liquefied phase has a higher oxygen content, which is confirmed by the elemental analysis data below. The amount of solid material formed, calculated on the dry biomass, was only 1.2% w / w, despite the low reaction temperature. Taking into account the sawdust ash content of 0.6%, the amount of solid product is low.
[0097] Elemental analysis data for the organic liquid phase were C 84.0%, H 13.5%, N 0.06%, S 0.0%, O 2.2%, others 0.31%.
[0098] Elemental analysis data for the THF-soluble liquid phase was C 79.8%, H 8.8%, N 0.55%, S 0.3%, O 9.5%, others 1.07%.
[0099] Table 5 shows the organic liquid phase of Example 4.1 H-NMR (CDCl3) results (normalized integral value) are shown. [Table 5]
[0100] Table 6 shows the organic liquid phase of Example 4. 31 The hydroxyl numbers measured by P-NMR are shown. [Table 6]
[0101] Figure 5 shows the TGA data for the organic liquid product phase of Example 4. The dashed line indicates the boiling range of diesel.
[0102] Table 7 shows the THF soluble liquefied phase of Example 4. 1 The results of H-NMR (DMSO-d6) (normalized integral value) are shown. [Table 7]
[0103] Table 8 shows the THF soluble liquefied phase of Example 4. 31 The hydroxyl numbers measured by P-NMR are shown. [Table 8]
[0104] Figure 6 shows the TGA data for the THF soluble liquefied phase of Example 4. The dashed line indicates the boiling range of diesel.
Claims
1. 1. A method for converting a lignocellulosic starting material into an organic liquefaction product, characterized in that a first hydrotreatment step comprises mixing the lignocellulosic starting material with an amorphous, unsupported molybdenum sulfide catalyst comprising one or more of the following elements: iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), and a cofeed, thereby obtaining a mixture, and exposing the mixture to a stoichiometric or greater amount of hydrogen at elevated pressure and at a temperature between 270°C and 450°C, thereby producing the organic liquefaction product.
2. 2. The method of claim 1, wherein the molar fraction of sulfur (S) relative to the content of molybdenum (Mo) in the amorphous and unsupported molybdenum sulfide catalyst is from 0.1 to 2.3, optionally from 0.1 to 1.
0.
3. 3. The method according to claim 1 or 2, wherein the molar fraction of the one or more elements, i.e. iron (Fe), tungsten (W), cobalt (Co), vanadium (V) and ruthenium (Ru) relative to the molar fraction of molybdenum (Mo) in the amorphous and unsupported molybdenum sulfide catalyst is between 0.1 and 0.3, optionally between 0.1 and 0.
2.
4. The method according to any one of claims 1 to 3, wherein the elevated pressure is a pressure of from 50 to 300 bar.
5. 5. The method of claim 1, wherein the catalyst is introduced into the mixture of lignocellulosic starting material in the form of a slurry of catalyst particles in a liquid cofeed.
6. 6. The process according to any one of claims 1 to 5, wherein the co-feed is selected from vegetable oils and vegetable fats, such as tall oil and tall oil pitch, pyrolysis oils, HTL oils, animal fats, fatty acids, fossil or renewable liquid hydrocarbons, and / or recycle or recycled products of products obtained in the process or fractions of products obtained in the process.
7. 7. The method according to any one of claims 1 to 6, wherein the co-feed is a mixture of vegetable oils and / or animal fats with fossil and / or renewable hydrocarbons.
8. 8. The method according to any one of claims 1 to 7, wherein the lignocellulosic starting material has a dry content of more than 50 wt%, preferably between 70 and 95 wt%, most preferably between 80 and 92 wt%.
9. 9. The method according to any one of claims 1 to 8, wherein the lignocellulosic starting material is selected from forest residues selected from wood chips and / or sawdust, bark and / or roots and / or branches, wood that has been subjected to a drying or torrefaction process, lignocellulosic originating from agriculture, such as straw from crops such as oats, wheat, barley and rye, corn stover, grasses and herbs, fodder crops, oat husks, rice husks, construction waste containing at least 50% by weight of material of lignocellulosic origin, and mixtures thereof.
10. 10. The method of any one of claims 1 to 9, wherein the lignocellulosic starting material has not been subjected to a thermochemical treatment, such as pyrolysis or hydrothermal liquefaction, prior to being subjected to the process.
11. 11. The method of any one of claims 1 to 10, wherein the process comprises at least a second conversion step following the first hydrotreating step, which second conversion step may be a single step.
12. 12. The method of any one of claims 1 to 11, wherein the mixture is exposed to a temperature of from 300°C to 380°C.
13. In a molybdenum sulfide catalyst containing one or more of the following elements (E), namely iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), the catalyst has an empirical formula for molybdenum (Mo), the one or more elements (E), and sulfur (S), namely Mo x E y S z having In the above, x=1, 0.1<y<0.3, and z≦2.
3. A molybdenum sulfide catalyst comprising:
14. 14. The catalyst of claim 13, wherein the catalyst is substantially amorphous as determined by X-ray powder diffraction analysis and optical microscopy using polarized light.
15. Catalyst according to claim 13 or 14, wherein the particle size distribution of the catalyst has a median value of 1 to 500 μm, preferably 1 to 200 μm, as determined by laser diffraction.
16. 16. The catalyst of any one of claims 13 to 15, wherein z≦1.
0.
17. 17. A method for converting a lignocellulosic starting material into one or more liquid and / or aqueous phases and a hydrocarbon phase, comprising exposing a mixture of the lignocellulosic starting material, the catalyst of any one of claims 13 to 16 and a cofeed to stoichiometric or greater amounts of hydrogen, elevated pressure and a temperature of 270°C to 450°C, thereby producing one or more liquid and / or aqueous phases and a hydrocarbon phase.
18. 1. A method for producing a molybdenum sulfide catalyst containing one or more of the following elements (E): iron (Fe), tungsten (W), cobalt (Co), vanadium (V), and ruthenium (Ru), comprising the steps of: - MoO 3 And (NH 4 ) 2 forming a first reaction mixture by combining S with water; pressurizing the first mixture using hydrogen gas and heating and stirring the mixture; - forming a second mixture by adding a hydrocarbon fraction having a kinematic viscosity of less than 2.0 CSt @ 40°C and metal salts of Fe and / or W and / or Co and / or V and / or Ru, such as sulfates and / or nitrates of Fe, W, Co, V and Ru, at an appropriate pressure and temperature; pressurizing said second mixture with hydrogen gas and heating said second mixture using a suitable temperature gradient; - removing water and a portion of the hydrocarbon fraction by reducing the pressure of the second mixture and heating the residual hydrocarbons to a suitable temperature; and - Recovering the catalyst in the form of a slurry with residual hydrocarbons. The process includes: A method for producing a molybdenum sulfide catalyst.
19. In the step of forming a second mixture, metal salts of Fe and / or W and / or Co and / or V and / or Ru, such as sulfates and / or nitrates of Fe, W, Co, V and Ru, are mixed with molybdenum (Mo), the one or more elements (E), and sulfur (S) according to an empirical formula: Mo x E y S z in an amount to provide a catalyst having In the above, x=1, 0.1<y<0.3, and z≦2.
3.
20. The method of claim 18.